MANAJEMEN KONFLIK MADRASAH PASCA PANDEMI COVID- 19 DI WILAYAH TAPAL KUDA - Husnan, Riayatul; Hidayat, Rofiq; Machfudz (re-JIEM (Research Journal of Islamic Education Management), 2023)
The Covid-19 pandemic has created new conflicts within educational institutions, especially madrasas. Moreover, the Tapal Kuda is an area that has a different culture and language so it requires proper conflict management. For this reason, this research is focused on three places, namely MAN 1 Jember, MAN Bondowoso, and MAN 2 Banyuwangi which are in the center of the Tapal Kuda. The purpose of this study is to describe the process of identification, classification, and problem-solving strategies related to conflict management in Madrasas after the Covid-19 pandemic in the Tapal Kuda area. Data mining using observation, documentation, and semi-structured interviews. Data analysis used the Miles and Huberman models, testing the validity of the data using technical triangulation. The results showed that 1) The process of identifying post-covid-19 madrasa conflict management problems in the Tapal Kuda area based on Tosi's conflict theory is still in the first stage in the form of antendants of conflict, 2) The majority conflict classification process is with intragroup, for MAN 2 Banyuwangi with intragroup and intergroup because it deals with stakeholders outside the school, 3) Conflict resolution strategies are in an integrative style because the three madrasas involve many parties and remain open to suggestions and criticism.